Prognostic value of hepatic venous pressure gradient in patients with compensated chronic hepatitis C-related cirrhosis. (April 2013) - Rincón, Diego; Lo Iacono, Oreste; Tejedor, Marta; Hernando, Ana; Ripoll, Cristina; Catalina, María-Vega; Salcedo, Magdalena; Matilla, Ana; Senosiain, María; Clemente, Gerardo; Molinero, Luis-Miguel; Albillos, Agustín; et al.
Abstract Background and aim. Hepatic venous pressure gradient (HVPG) is the main predictor of clinical decompensation in cirrhotic patients with compensated disease of any etiology without varices. However, the predictive factors of decompensation are not so well known in patients with hepatitis C-related compensated cirrhosis, in whom etiology-based therapy is difficult. The aim of this study was to identify predictors of decompensation in patients with compensated chronic hepatitis C (CHC)-related cirrhosis with and without esophageal varices (Baveno stages 1 and 2). Methods. The study population was a cohort of 145 of such consecutive patients who received hepatic hemodynamic study. All patients were similarly followed every 6 months. Through multivariate Cox regression and bootstrap analyses, a prognostic index (PI) was developed and tested in an external cohort (n = 38). Results. Forty-two patients (29%) suffered a first decompensation episode after a median follow-up of 27 months (2–110). Cox regression analysis identified HVPG (hazard ratio (HR) 1.11; 95% confidence interval (CI): 1.05–1.17) and albumin (HR 0.42; 95% CI: 0.22–0.82) as independent predictors of decompensation. Bootstrapping confirmed that HVPG (95% CI: 1.05–1.18) and albumin (95% CI: 0.12–0.74) were the most robust predictive variables. Using a cut-off level of 2.5, the PI [4 + (0.11 × HVPG - 0.8 × albumin)] was able to distinguish two populations of patients with very different risks of decompensation in both the exploratory and validation cohorts. A time-dependent ROC curve identified HVPG as the best predictive variable. Conclusion. HVPG and albumin are independent predictors of clinical decompensation in patients with compensated CHC-related cirrhosis irrespective of the existence of varices.